2008
DOI: 10.1038/ni.1617
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor Erg is essential for definitive hematopoiesis and the function of adult hematopoietic stem cells

Abstract: Ets-related gene (ERG), which encodes a member of the Ets family of transcription factors, is a potent oncogene. Chromosomal rearrangements involving ERG are found in acute myeloid leukemia, acute lymphoblastic leukemia, Ewing's sarcoma and more than half of all prostate cancers; however, the normal physiological function of Erg is unknown. We did a sensitized genetic screen of the mouse for regulators of hematopoietic stem cell function and report here a germline mutation of Erg. We show that Erg is required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
240
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 248 publications
(248 citation statements)
references
References 54 publications
6
240
2
Order By: Relevance
“…Bone marrow was harvested from 7-12 week-old C57BL/6 mice then fractionated by using antibody combinations as described previously (24).…”
Section: Methodsmentioning
confidence: 99%
“…Bone marrow was harvested from 7-12 week-old C57BL/6 mice then fractionated by using antibody combinations as described previously (24).…”
Section: Methodsmentioning
confidence: 99%
“…A more modest reduction in megakaryocyte progenitor cells was evident in the tissues of Erg ϩ/ Mld2 mice, as described in ref. 12. In Fli-1 ϩ/Ϫ mice, the numbers of these cells was normal ( Fig.…”
Section: A Genetic Interaction Between Fli-1 and Ergmentioning
confidence: 99%
“…Analyses of Erg ϩ/Mld2 adult mice revealed that Erg is required for normal adult HSC homeostasis. HSCs are reduced in number in Erg ϩ/Mld2 mice and unable to compete effectively with Erg ϩ/ϩ cells to reconstitute irradiated transplant recipients (12).…”
mentioning
confidence: 99%
“…The erythroblastosis virus E26 transforming sequence (ETS) encodes the ETS-related gene (ERG) that has an important physiological role in hematopoiesis (Loughran et al, 2008), angiogenesis (Birdsey et al, 2008), vascular (Ellett et al, 2009) and bone development (Iwamoto et al, 2007). ERG belongs to the highly conserved ETS transcription factor family that is defined by the ETS DNA-binding motif 5 0 -GGA(A/T)-3 0 (Sharrocks, 2001;Wei et al, 2010).…”
Section: Introductionmentioning
confidence: 99%